250 M Ultra Deep Milled Diaphragm Wall: The New Frontier for the Cut off Wall Depth has Been Doubled by Trevi Group Technology - Stefano Trevisani; Daniele Vanni; Maurizio Siepi; Pagliaccim Federico (Deep Foundations Institute, 2014)
"Abstract: The paper describes a large innovative project completed in 2012-20123 by Trevi Group, to develop equipment capable to install ultra-deep diaphragm wall. The project highlights the capacity of SOILMEC to design and build a new hydromill able to reach an unprecedented depth of 250 m, including new devices for monitoring and correct the verticality. The entire project can take advantage of the long and solid experience matured by Trevi and Rodio (now part of Trevi Group), developing in house or, else, select the elements necessary for a high quality product in the ground.The paper describes the results of different systems used to monitor and control the verticality and the twist of panel during excavation, together with the method used to pour concrete. Finally, the results of verification coring and lab tests on concrete samples recovered at various depths are discussed. The test field has been supervised by representatives of three of the major Italian Universities, and lasts almost one year from August 2012 to June 2013.The verification holes made use of an innovative combination of directional drilling and coring, to check the quality of the plastic concrete for the full length of the panel. The data confirmed that the test panel has high quality concrete, meeting or exceeding to the prefixed requirements.With this test, super-deep cut-off walls reaching depths of 250 m have become a reality. This would change the perspectives of dam engineering both for existing dams rehabilitation and for new dams design and construction. With the execution of this test panel, the technology of milled concrete cutoffs has made a ”quantum leap”, pushing the limit of practicable dams."